A long ride in Texas : the explorations of John Leonard Riddell - Riddell, John Leonard, 1807-1865 (Centennial series of the Association of Former Students, Texas A & M University, 1994)
John was a medical Doctor, geoglist, and botanist who traveled from New Orleans to Texas 1839,surveying the Texas Hill country for a group of for businessmen searching for the lost San Saba Silver mine.